TAFSIR JALÂL AL-DÎN AL-SUYÛTÎ & IBN JARÎR AL-TABARÎ PADA AL-MÂIDAH: 51 (Studi Tafsir Muqâran) - komarudin komarudin (Fakultas Ushuluddin dan Studi Islam, 2022)
Abstract This article aims to reveal the interpretation of Jalaladdîn al-Suyûtî and Ibn Jarîr al-Tabarî about making Jews and Christians as leaders through their interpretation of the Qur'an in Surah al-Mâidah verse 51 and introduce the interpretation of muqāran. In fact, much literacy regarding to interpretations of al-Maidah verse 51 have been found, but among these literacy do not show the main source so that it feels far from substance. Helmy Zakaria for example, he wrote “VARIETY OF NETIZEN'SINTERPRETATIONS ABOUT NON-MUSLIM LEADERS; Study on theInterpretation of Surah al-Maidah verse 51